How to Apply Augmented Reality based Active Learning in Islamic Higher Education? - Anisa Jaya Rahmawati; Gunarhadi Gunarhadi; Moh. Muchtarom (Proceedings Series on Physical & Formal Sciences, 2022)
Learning at Islamic universities currently has challenges to utilize technology-based active learning. However, knowledge about the application of learning media based on active learning in Islamic higher education is still very lacking. So there needs to be a discussion about this. The purpose of this study was to determine the pattern of implementation and strategy of applying augmented reality based on active learning in Islamic universities. Based on the results of the study, it shows the implementation pattern and learning strategy of augmented reality-based on active learning in Islamic Universities as follows: First, it begins by considering the development of the application, knowing the types of active learning classroom, introducing augmented reality learning media and active learning, giving pictures and videos of learning materials using augmented reality for the process of individual reflection and the last stage is discussion and group work. The application of augmented reality in learning in Islamic higher education also attention to indicators of student participation behavior so that students have intellectual inquiry abilities and metacognition.